Old Wabaunsee, Wabaunsee County - Rivers, James C. (Kansas State University, The Chapman Center for Rural Studies, 2009)
James C. Rivers traces the life of an early African American female homesteader, Dicy Nichols. Buying a modest farm in 1867, Dicy Nichols lived there and raised a family until selling her land in 1883 to the Hart-Enlow Ranch. She stayed on the land as a tenant. The author provides photographs of the original site of her land in northern Wabaunsee County, as well as evidence drawn from land records and local recollections.
James C. Rivers, “Old Wabaunsee, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/9.
Keywords: Dicy Nichols; Hart-Enlow Ranch; James C. Rivers; Wabaunsee County